SISTEM INFORMASI SEKOLAH SPS PAUD BALKAM CERIA BERBASIS WEBSITE - Dwiki Airlambang, .. (2022)
The website information system is one of the important things in a school's needs. SPS Paud Balkam Ceria is a provider of educational services for early childhood who need a website-based information system because the dissemination of information and the registration process still uses a manual system. To meet these needs, it is necessary to develop website-based technology. Preventing the loss of files or registration documents and the dissemination of information that is still inadequate can help schools more easily manage this. In developing the system, researchers used the waterfall method to adjust the needs of the system developed through observations to schools. The information system was created using Visual Studio Code in coding and using the Laravel framework to assist researchers in creating an attractive display. It is hoped that the creation of this system can be the right alternative to be a solution to the problems experienced by schools.